Rectification of the nomenclature concerning the Oligo-Miocene freshwater ichthyofauna of Bohemia - Gaudant,J. (Journal of the Czech Geological Society, 1996)
The author’s purpose is to put the zoological nomenclature used for the Oligo-Miocene fish-fauna of Bohemia in agreement with the International Code of Zological Nomenclature: Pirskenius diatomaceus Obrhelova, 1961 has been called Gobius gracilus (Laube), Leuciscus (Palaeoleuciscus) socoloviensis Obrhelova, 1969 is being transferred to Palaeoleuciscus chartaceus (Laube), Leuciscus (Palaeoleuciscus) luzicensis Obrhelova, 1969 to Palaeorutilus medius (Reuss) and Varhostichthys brevis (Agassiz) to Protothymallus elongatus (Kramberger). The reexamination of the holotypes of two problematical species of Miocene fossil fishes from Bohemia, „Lepidosteus“ bohemicus Laube, 1901 and Esox destructus Laube 1901 has revealed their dubious nature.
Keywords: fishes; Oligocene; Miocene; Cyprinidae; Esocidae; Gobiidae